Perspektif Pemasaran Media Sosial Tiktok Terhadap Minat Beli Produk Kosmetik - Sutrisno, Niantoro; Ria Estiana; Fitriyah Azriyani (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
Today's modern world cannot be separated from various digital platforms used in the company’s marketing. One social media platform that is experiencing rapid growth in users is Tiktok, a digital platform that allows users to share videos. Currently, the Tiktok social media platform is used by 112 million Indonesians or second in the world after 116 million users in the United States (data from the website data.goodstats.id). However, in Indonesia the use of the Tiktok social media platform has not been optimally used as part of the company's product marketing strategy. Based on these conditions, this research was conducted with the aim of examining and identifying the influence of Tiktok Social Media on Interest in Buying Cosmetic Products. The method used in this research is a quantitative method with a survey approach. Meanwhile, data collection was carried out by distributing questionnaires to 100 students from 3 universities in Bekasi Regency. The results of the analysis of the processed data show that Tiktok Social Media Marketing has an influence on Interest in Buying Cosmetic Products.